2022
DOI: 10.1002/lno.12040
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of phytoplankton responses to summer wind events in a stratified lake: A modeling study

Abstract: Extreme wind events affect lake phytoplankton by deepening the mixed layer and increasing internal nutrient loading. Both increases and decreases in phytoplankton concentration after strong wind events have been observed, but the precise mechanisms driving these responses remain poorly understood or quantified. We coupled a one-dimensional physical model to a biogeochemical model to investigate the factors regulating short-term phytoplankton responses to summer wind events, now and under expected warmer future… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 87 publications
(130 reference statements)
1
7
0
Order By: Relevance
“…The high positive dependence of Chla area on Z mix found in this study is generally consistent with models that predict an increase in phytoplankton biomass with a deepening mixed layer (Berger et al, 2006; Diehl, 2002; Mesman et al, 2022). These findings are supported by results from enclosure experiments, where artificial deepening of the mixed layer typically increases phytoplankton growth and biomass (Cantin et al, 2011; Diehl et al, 2002; Giling et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The high positive dependence of Chla area on Z mix found in this study is generally consistent with models that predict an increase in phytoplankton biomass with a deepening mixed layer (Berger et al, 2006; Diehl, 2002; Mesman et al, 2022). These findings are supported by results from enclosure experiments, where artificial deepening of the mixed layer typically increases phytoplankton growth and biomass (Cantin et al, 2011; Diehl et al, 2002; Giling et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Ecological activities in shallow lakes are also affected by winddriven lake environments. There are differences in the adaptability of phytoplankton to a series of changes in lake environments, resulting in an entirely new competition for nutrients, light energy and buoyancy regulation (Mesman et al, 2022). Therefore, biological species that can quickly absorb and store nutrients and grow well in low light can get growth advantages, and eventually, the biological community is restructured (Ptacnik et al, 2010).…”
Section: Impacts Of Wind-driven Hydrodynamics On Water Quality and Ec...mentioning
confidence: 99%
“…Under the catastrophic events of short-term hurricanes, submersed and emergent macrophytes in shallow lakes and even in deep lakes were uprooted (James et al, 2008;Stockwell et al, 2020), the spatial distribution of both micro-and macro-zooplankton changed substantially, and even the fishery collapsed (Havens et al, 2011). Previous studies have shown that extreme wind events still have an increasing trend in various regions (e.g., Western Europe), including intensification of intensity, duration and frequency, which may have an aggressive impact on the structure and function of lake ecosystems (Mesman et al, 2022). Clearly, the global influence of extreme events on lake ecosystems warrants further study.…”
Section: Hurricanes Impact On Lakesmentioning
confidence: 99%
“…In this study, a PB hydrodynamic lake model, GOTM (General Ocean Turbulence Model; Burchard et al, 1999), was used to generate water temperature profiles and other hydrodynamic metrics. GOTM also served as the foundation of water quality simulations made with the SELMAPROT-BAS model (Mesman et al, 2022) that is coupled to GOTM through the Framework for Aquatic Biogeochemical Models (FABM; Bruggeman and Bolding, 2014).…”
Section: Process-based (Pb) Lake Modelmentioning
confidence: 99%